DEKONSTRUKSI FILSAFAT PERADABAN SIR MUHAMMAD IQBAL - Ammar Fauzi (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This paper tries to construct the philosophy of Iqbal's civilization thought by using the theory of four causes of Aristotle. It is concluded that the steps to achieve the philosophy of superior civilization are first, the actor of civilization must recognize themselves (Khudi). Achievement of Khudi means he has met with God, after that the actor of civilization must return to nature to fuse (absence) with the community, manage nature with the principles of divinity (bi-Khudi). Then civilization actors dialectic with history to determine the prototype of civilization. From the dialectical results, then it is chosen the era of the prophet who has the characteristics of civilization across regions and races, and not based on blood.